Above-room-temperature ferroelectricity and piezoelectric activity of dimethylglycinium-dimethylglycine chloride. (August 2022) - Szafrański, M.; Tylczyński, Z.; Wiesner, M.; Czarnecki, P.; Ghazaryan, V.V.; Petrosyan, A.M.
Graphical abstract: Highlights: A derivative of glycine, the simplest proteinogenic amino acid, was used to synthesize a new hybrid organic–inorganic ferroelectric material. The crystal exhibits a high-temperature Curie point at 401 K, favourable for practical applications. Ferroelectric properties are associated with the piezoelectric activity of the crystal that persists in a wide temperature range. The piezoelectric performance of the crystal increases several times as the Curie point is approached. Abstract: Heavy-metal-free ferroelectrics are sought as environmentally compatible alternatives to commonly used inorganic oxides. Here, we demonstrate direct evidence of the ferroelectric properties of a hybrid organic–inorganic material, dimethylglycinium-dimethylglycine chloride. At room temperature, the compound crystallizes in the polar space group P 21 and exhibits a switchable spontaneous polarization of 1.9 μC cm −2 . Ferroelectric properties are preserved in a wide temperature range up to about 401 K, where the crystal undergoes the transition to the paraelectric phase of the space group P 21 / c . The temperature-dependent single-crystal X-ray diffraction study and the calorimetric data indicate an order–disorder contribution to the transition mechanism, which is consistent with the critical slowing down of the dielectric relaxation observed near the Curie point. The spontaneous polarization results from ionic displacements that are induced by changes in the disordering of the dimeric cations. In the ferroelectric phase, the crystal exhibits remarkable piezoelectric activity. The electromechanical and elastic properties of the material were thoroughly characterized.